The boy in the striped pyjamas : a fable - Boyne, John, 1971- (Oxford ; New York : David Fickling Books, 2010)
Bored and lonely after his family moves from Berlin to a place called "Out-With" in 1942, Bruno, the son of a Nazi officer, befriends a boy in striped pajamas who lives behind a wire fence.
Young Adult.
Young Adult
Keywords: Auschwitz (Concentration camp) -- Juvenile fiction; Auschwitz (Concentration camp) -- Fiction; Auschwitz (Concentration camp) -- Fiction; Concentration camps -- Poland -- Juvenile fiction; Friendship -- Juvenile fiction; Holocaust, Jewish (1939-1945) -- Juvenile fiction; Nazis -- Juvenile fiction; World War, 1939-1945 -- Jews -- Juvenile fiction; Concentration camps -- Poland -- Fiction; Friendship -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Nazis -- Fiction; World War, 1939-1945 -- Jews -- Fiction; Concentration camps -- Poland -- Fiction; Friendship -- Fiction; Holocaust, 1939-1945 -- Fiction; National socialism -- Fiction; World War, 1939-1945 -- Fiction